2020
DOI: 10.1016/j.pbb.2019.172837
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic mechanisms underlying the rapid and sustained antidepressant actions of ketamine

Abstract: Clinical and preclinical studies have demonstrated that depression, one of the most common psychiatric illnesses, is associated with reduced levels of neurotrophic factors, including brainderived neurotrophic factor (BDNF) and vascular endothelial growth factor (VEGF), contributing to neuronal atrophy in the prefrontal cortex (PFC) and hippocampus, and reduced hippocampal adult neurogenesis. Conventional monoaminergic antidepressants can block/reverse, at least partially, these deficits in part via induction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(100 citation statements)
references
References 149 publications
2
95
0
3
Order By: Relevance
“…Thus, it is interesting that antidepressant effects of KET are continued to be observed even when KET has been eliminated from the rat's system. KET is a multi-modal drug and various mechanisms have been proposed for its rapid and long-lasting antidepressant action (reviewed in [53,[57][58][59]). For example, GluN2B containing NMDARs are reported to be involved in the rapid antidepressant actions of KET [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is interesting that antidepressant effects of KET are continued to be observed even when KET has been eliminated from the rat's system. KET is a multi-modal drug and various mechanisms have been proposed for its rapid and long-lasting antidepressant action (reviewed in [53,[57][58][59]). For example, GluN2B containing NMDARs are reported to be involved in the rapid antidepressant actions of KET [60].…”
Section: Discussionmentioning
confidence: 99%
“…It will be interesting to investigate the role of KET on GWI calcium homeostatic mechanisms and its subsequent effect on modulating the rapid behavioral response in this model. The fast-acting and long-lasting antidepressant effect of KET is also thought to involve augmentation of the neurotrophic factor Brain-Derived Neurotrophic Factor (BDNF) [57,58]. Ongoing studies in our laboratory are assessing the role of BDNF signaling in GWI depression and its alteration following KET administration in GWI rats.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a single injection of ketamine activated the mammalian target of rapamycin (mTOR) and this enhanced synaptogenesis in the medial prefrontal cortex (mPFC) [16], reversing the stress-induced synaptic deficits in mice [17]. Ketamine administration led to the fast production of brain neurotrophic factor (BDNF) [18], an important mediator of MDD pathology and treatment [19], by inducing glutamate bursts and activating postsynaptic α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPA) receptors [20]. Similar to ketamine, in vitro [21] and in vivo [22] experiments showed that (2R,6R)-HNK induced structural and synaptic plasticity.…”
mentioning
confidence: 99%
“…It was also discovered that ADGRB2 regulates the transcription of vascular endothelial growth factor (VEGF) by activating the repressor GA-binding protein [ 104 ]; as such, ADGRB2 helps regulate angiostatic function in the brain, resulting in an inverse correlation between the expression levels of ADGRB2 and VEGF [ 96 ]. These findings pointed to the ADGRB2 regulation of VEGF as a potential pathway to control hippocampal neurogenesis and, therefore, alter mood-related behaviors [ 22 , 65 ]. Such an intriguing hypothesis remains to be tested directly, as shown in Figure 1 .…”
Section: Systematic Analysis Of Ogpcrs In Anxiety and Mood Disordementioning
confidence: 99%
“…More recently, evidence of the involvement of further signaling pathways and receptor systems prompted the drug discovery enterprise to move beyond the monoaminergic systems. Particularly, the observation that the glutamatergic modulator, ketamine, elicits fast-acting antidepressant responses has driven an intensive research effort that culminated with the recent approval of ketamine for treatment-resistant depression, not without raising concerns about its safety [ 18 , 19 , 20 , 21 , 22 ]. The pharmacological treatment of patients diagnosed with bipolar disorder (BPD) consists of mood stabilizing medicines, with lithium remaining the most effective treatment almost seventy years after its serendipitous discovery [ 23 ].…”
Section: Introductionmentioning
confidence: 99%